The Analysis of Business Feasibility of Bottled Water Product In Cup Of 240 ml In PDAM Tirta Binangun, Kabupaten Kulon Progo - Mahendra, Abyan; Anoraga, Satria Bhirawa (Journal of Agri-Food Science and Technology, 2020)
Regional Drinking Water Company (PDAM) Tirta Binangun is one of the Regional Owned Enterprises (BUMD) in the field of water delivery services for Kulon Progo residents. PDAM Tirta Binangun also has a Bottled Drinking Water (AMDK) production program. AMDK KU needs to identify the financial feasibility of a 240 mℓ cup product. The need for business analysis is to find out whether AMDK KU can generate profits in the future or vice versa. The analysis of business feasibility used the methods of Break Event Point (BEP), Net Present Value (NPV), and Net B/C Ratio. Besides, it is necessary to take alternative corrective actions at the company for 240 mℓ cup products. The company of AMDK KU has gotten the normal BEP for the first cup production of 240 mℓ is 70,654 cartons, and the income in 6 months and 15 days is Rp 1,130,470,076. The analysis result is the company of AMDK KU, with the cup production of 240 mℓ, can be said that it had a profit. If the income and the price are increased by 10 percent, 20 percent, and 30 percent, it still will have profit. According to the NPV analysis, the products of 240 mℓ cup of AMDK KU are feasible to be done, even for 10 days later. However, the analysis result of the Net B/C Ratio, the products of 240 mℓ cup of AMDK KU is profitable because the score is Rp 1.1332. Furthermore, the PP result found in 10 months 11 days is included as a quick return on investment. The alternative action to solve the unprofitable products is by developing the product using the new innovation, product branding, a new marketing strategy, and additional investment.